The need for a functional pharmaceutical industry in Sierra Leone: lessons from the COVID-19 pandemic - Eugene Conteh; Melody Okereke; Foday Umaro Turay; Alhaji Sununu Bah; Abdulwasiu Muhsinah (Journal of Pharmaceutical Policy and Practice, 2022)
With an estimated population of 8.3 million, Sierra Leone has no existing pharmaceutical manufacturing company at present. The recent COVID-19 pandemic brought to the limelight the fragility and weakness of the Sierra Leonean pharmaceutical industry as it resulted in severe drug shortages and medicine insecurity in the country due to the restrictions imposed on importations, which validates the uncertainties if the country can sufficiently meet its local pharmaceutical needs and health demands. In this paper, we highlight the current situation of the Sierra Leonean pharmaceutical sector and provide recommendations for the country towards building a functional pharmaceutical industry based on lessons learnt from the COVID-19 pandemic.